Plaza Ramón Castilla - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: The square and the Ramón Castilla statue of Iquitos are observed
ENGLISH: Se observa la plaza y la estatua Ramón Castilla de Iquitos

SPANISH: The square and the Ramón Castilla statue of Iquitos are observed
ENGLISH: Se observa la plaza y la estatua Ramón Castilla de Iquitos
Ramon Castilla Square
Keywords: Iquitos (Perú)|~|Iquitos antiguo|~|Perú--Cultura|~|Perú--Patrimonio Cultural